2018
DOI: 10.1590/s0102-053620180203
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance and genetic dissimilarity among cherry tomato genotypes

Abstract: The genotypes evaluation in a germplasm bank is essential to determine their commercial or usefulness, as potential parents, in a breeding program. We aimed to detect the genetic diversity of 42 tomato genotypes of cherry type, belonging to the germplasm bank of the Federal University of Uberlândia and, also evaluate their behavior. The experiment was conducted in a greenhouse in randomized block design with 42 treatments and two replications. Ten quantitative traits of agronomic importance were evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The dendrogram exhibited a cophenetic correlation coefficient of 0.88 and significance according to the t test (p<0.01), making it a satisfactory tool to represent the information in the matrix and subsequent group formation. In other studies on tomato crops, the UPGMA method was also efficient at discriminate groups (Araujo et al, 2016;Maciel et al, 2018a;Peixoto et al, 2018). With the 30% cutoff point in the dendrogram, the populations formed three distinct groups.…”
Section: Resultsmentioning
confidence: 79%
“…The dendrogram exhibited a cophenetic correlation coefficient of 0.88 and significance according to the t test (p<0.01), making it a satisfactory tool to represent the information in the matrix and subsequent group formation. In other studies on tomato crops, the UPGMA method was also efficient at discriminate groups (Araujo et al, 2016;Maciel et al, 2018a;Peixoto et al, 2018). With the 30% cutoff point in the dendrogram, the populations formed three distinct groups.…”
Section: Resultsmentioning
confidence: 79%
“…Through this method, genetic dissimilarity was found between the BC 1 F 3 populations, parents, and the commercial cultivar by the formation of five groups. This methodology is traditionally used to represent genetic dissimilarity among tomato plant populations in various segments ( Maciel et al, 2018 , Finzi et al, 2020 , Peixoto et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Characterizing and analyzing the genetic dissimilarity of populations are essential for distinguishing divergent and promising genotypes ( Maciel et al, 2018 ). Traditionally, multivariate techniques have been used, such as dendrograms, the Tocher grouping method, canonical variables, and principal components to characterize the germplasms of normal tomato plants ( Maciel et al, 2018 , Alsamir et al, 2019 , Peixoto et al, 2020 ) and dwarf tomato varieties ( Finzi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of coincident groups, through the use of complementary methods of multivariate analysis, is also described in pepper (Negreiros & Miqueloni, 2013), passion fruit (Paiva et al, 2014), tomato (Luz et al, 2016;Amaral Júnior et al, 2017;Maciel et al, 2018b), which shows consistency of similarity results in the groups composition. The results obtained in the present study corroborate those found by these authors.…”
Section: Resultsmentioning
confidence: 98%